Workshop Rancang Bangun Jaringan Berdasarkan SKKNI Level 2 Bagi Siswa Kelas XII Jurusan Teknik Komputer dan Jaringan SMKN 1 Kota Bengkulu - Yetman Erwadi; Erwin Dwika Putra; Monsya Juansen (Program Studi Administrasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Bengkulu, 2022)
Since UKK is conducted by LSP, LSP is under the auspices of the National Professional Certification Agency (BNSP), meaning that the certificate issued by LSP is a national standard certificate. conducted by IDUKA. From the information we received from the head of the TKJ expertise program at SMKN 1 Bengkulu city, the average student pass for UKK from 2018 – 2022 is 45%, meaning that very many students fail. To overcome this problem the school has made various efforts, one of the efforts made is to bring guest teachers to the school where this activity is in the form of a workshop. The aim of this workshop is to improve hard skills as well as mental provision, tips and tricks when facing exams. The method used first is Needs Analysis At this stage an analysis of what is needed, both physical and non-physical needs, so that nothing is forgotten during the implementation of activities, or this stage can also be called concept maturation, Instrument Preparation (materials and practical tools) This stage is the holding of preparation and making of any material that will be delivered, and preparing what tools are needed to support practical activities, Implementation of Activities Activities take place in the TKJ Expertise Program Labor room, activities last for 2 days. As previously stated, the method of activity is the lecture, discussion, and practice method. Students listen to the theoretical material delivered, after the theoretical material is delivered then enter the practical session, where in this practice session at the same time discussions are held if there are things that are asked by students related to the practical activities carried out. Then to measure the ability of each student a simulation exam is held at the end of the session, the evaluation stage is held to evaluate the entire series of activities, the results of this evaluation will become material for future follow-up plans. The hope for class XII students majoring in TKJ can improve their hard skills and be able to do UKK well.